Transference, descriptions, and notes on Cuban Graciliini (Coleoptera, Cerambycidae, Cerambycinae) - Devesa, Sergio; Santos-Silva, Antonio (Zootaxa, 2021)
Merostenus exiguous Zayas, 1975 (currently, Caribbomerus exiguus) is transferred to Perigracilia Linsley, 1942. Information on the type series of M. exiguous is provided, and a lectotype is designated to the species. Two new species of Caribbomerus are described from Cuba: C. elieri, and C. zayasi.